Activated ephrinA3/EphA4 forward signaling induces retinal ganglion cell apoptosis in experimental glaucoma. (1st November 2020) - Xu, Lin-Jie; Gao, Feng; Cheng, Shuo; Zhou, Zhi-Xin; Li, Fang; Miao, Yanying; Niu, Wei-Ran; Yuan, Fei; Sun, Xing-Huai; Wang, Zhongfeng
Abstract: Previous studies have demonstrated that EphA4 participates in neuronal injury, and there is a strong interaction between ephrinA3 and EphA4. In this study, we showed that in a rat chronic ocular hypertension (COH) experimental glaucoma model, expression of EphA4 and ephrinA3 proteins was increased in retinal cells, including retinal ganglion cells (RGCs) and Müller cells, which may result in ephrinA3/EphA4 forward signaling activation on RGCs, as evidenced by increased p-EphA4/EphA4 ratio. Intravitreal injection of ephrinA3-Fc, an activator of EphA4, mimicked the effect of COH on p-EphA4/EphA4 and induced an increase in TUNEL-positive signals in normal retinas, which was accompanied by dendritic spine retraction and thinner dendrites in RGCs. Furthermore, Intravitreal injection of ephrinA3-Fc increased the levels of phosphorylated src and GluA2 (p-src and p-GluA2). Co-immunoprecipitation assay demonstrated interactions between EphA4, p-src and GluA2. Intravitreal injection of ephrinA3-Fc reduced the expression of GluA2 proteins on the surface of normal retinal cells, which was prevented by intravitreal injection of PP2, an inhibitor of src-family tyrosine kinases. Pre-injection of PP2 or the Ca 2+ -permeable GluA2-lacking AMPA receptor inhibitor Naspm significantly and partially reduced the number of TUNEL-positive RGCs in the ephrinA3-Fc-injected and COH retinas. Our results suggest that activated ephrinA3/EphA4 forward signaling promoted GluA2 endocytosis, then resulted in dendritic spine retraction of RGCs, thus contributing to RGC apoptosis in COH rats. Attenuation of the strength of ephrinA/EphA signaling in an appropriate manner may be an effective way for preventing the loss of RGCs in glaucoma. Highlights: EphrinA3/EphA4 signaling was activated on retinal ganglion cells (RGCs) in glaucoma. Activated ephrinA3/EphA4 signaling induced RGC dendritic spine retraction. Activated ephrinA3/EphA4 signaling induced RGC apoptosis. Activated ephrinA3/EphA4 signaling induced GluA2 endocytosis on RGCs. The GluA2-lacking AMPA receptor inhibitor Naspm reduced RGC apoptosis.